Spatial Analysis of Gravity Anomaly Over Maar Area of Lamongan Volcanic Field - Khafidh Nur Aziz; Jamilatusolikhah Jamilatusolikhah; Dini Agasti Rini; Yanuri Larasati; Al Ashfiya Bian Itsna Ashfa (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2020)
Lamongan Volcano located in, East Javahas basaltic cinder or spatter cones and maars.The presence of maar and cinder cones indicates active volcanic activity at their time.We used secondary gravity data from GGMplus. The result of residual anomaly map shows that Maar which is located on the NW of Lamongan Volcano shows a lineament pattern with Lamongan Volcano which is trending northwest-southeast and maar indicates a normal fault.